Metabolomics and 16S rRNA sequencing of human colorectal cancers and adjacent mucosa - Loke, Mun Fai; Chua, Eng Guan; Gan, Han Ming; Thulasi, Kumar; Wanyiri, Jane W.; Thevambiga, Iyadorai; Goh, Khean Lee; Wong, Won Fen; Vadivelu, Jamuna (Public Library of Science, 2018)
Colorectal cancer (CRC) is ranked the third most common cancer in human worldwide. However, the exact mechanisms of CRC are not well established. Furthermore, there may be differences between mechanisms of CRC in the Asian and in the Western populations. In the present study, we utilized a liquid chromatography-mass spectrometry (LC-MS) metabolomic approach supported by the 16S rRNA next-generation sequencing to investigate the functional and taxonomical differences between paired tumor and unaffected (normal) surgical biopsy tissues from 17 Malaysian patients. Metabolomic differences associated with steroid biosynthesis, terpenoid biosynthesis and bile metabolism could be attributed to microbiome differences between normal and tumor sites. The relative abundances of Anaerotruncus, Intestinimonas and Oscillibacter displayed significant relationships with both steroid biosynthesis and terpenoid and triterpenoid biosynthesis pathways. Metabolites involved in serotonergic synapse/ tryptophan metabolism (Serotonin and 5-Hydroxy-3-indoleacetic acid [5-HIAA]) were only detected in normal tissue samples. On the other hand, S-Adenosyl-L-homocysteine (SAH), a metabolite involves in methionine metabolism and methylation, was frequently increased in tumor relative to normal tissues. In conclusion, this study suggests that local microbiome dysbiosis may contribute to functional changes at the cancer sites. Results from the current study also contributed to the list of metabolites that are found to differ between normal and tumor sites in CRC and supported our quest for understanding the mechanisms of carcinogenesis.